SEPARATION OF LOW-INTENSITY MAGNETIC ANOMALIES AND ITS INTERPRETATION - HRYSHCHUK, P.; HURA, K.; NURMUKHAMEDOV, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
in the article the separation of low-intensity magnetic anomalies with method of averaging is executed. The selection of anomalies is analyzed for different radiuses of sliding window. The optimum radius of averaging is certain. Comparison of interpretation of the magnetic anomalies is executed at determination of their background constituent through spline and method of averaging.